Magneto-Elastic Effect in Non-Newtonian Ferrofluid Droplets Impacting Superhydrophobic Surfaces - V V S Vara Prasad, Gudlavalleti (Langmuir : the ACS journal of surfaces and colloids, 2021)
In this article, we propose, with the aid of detailed experiments and scaling analysis, the existence of magneto-elastic effects in the impact hydrodynamics of non-Newtonian ferrofluid droplets on superhydrophobic surfaces in the presence of a magnetic field. The effects of magnetic Bond number (Bom), Weber number (We), polymer concentration, and magnetic nanoparticle (Fe3O4) concentration in the ferrofluids were investigated. In comparison to Newtonian ferrofluid droplets, addition of polymers caused rebound suppression of the droplets relatively at lower Bom for a fixed magnetic nanoparticle concentration and We. We further observed that for a fixed polymer concentration and We, increasing magnetic nanoparticle concentration also triggers earlier rebound suppression with increasing Bom. In the absence of the magnetic nanoparticles, the non-Newtonian droplets do not show rebound suppression for the range of Bom investigated. Likewise, the Newtonian ferrofluids show rebound suppression at large Bom. This intriguing interplay of elastic effects of polymer chains and the magnetic nanoparticles, dubbed as the magneto-elastic effect, is noted to lead to the rebound suppression. We establish a scaling relationship to show that the rebound suppression is observed as a manifestation of the onset of magneto-elastic instability only when the proposed magnetic Weissenberg number (Wim) exceeds unity. We also put forward a phase map to identify the various regimes of impact ferrohydrodynamics of such droplets and the occurrence of the magneto-elastic effect